(untitled) (PANGEEA, 2025)
ABSTRACT: Hunedoara County 7016 km2 (3% of the total area of the country) lies in the central-western part of the country, between the Central and the Western Carpathians, in a mountainous area with a lot of valleys. From a historical point of view, it is situated between Transylvania and Banat. The variety of the natural environment and the richness of the cultural elements (artistic, ethnographic, historical) offers ethnographic complexity to the county which has six distinct parts: Momârlan Land, Haţeg Land, Strei Valley, Pădureni Land, Orăştie Land, Mureş Valley and Zarand Land.